Integration of Yoga Services in Public Health Service Delivery System in UT Of Jammu And Kashmir - Singh, Mohan; Raina, Rakesh Kumar; Gupta, Arun; Kotwal, Manjit; Tabassum, Ruhi; Hassan, Wahid Ul (International Research Journal of Ayurveda & Yoga, 2023)
Global Public health organizations are promoting Yoga as a health promotion intervention in Schools, workplaces, civil society, non governmental organizations and communities for prevention and management of diseases including Non-communicable, life style induced disorders, which require rational integration of Yoga services in Public Health Service Delivery system. Directorate of Ayush J&K is providing yoga services at community level through AHWCs. Work done reports of Yoga Instructors and District Ayush Offices were reviewed and analyzed. A google form based multiple choice questionnaire administered online to Yoga instructors to assess the practice trends, challenges in effective implementation of Yoga program of Ayush J&K. 71882 Yoga sessions have been organized out of which more than 69235 sessions were reportedly organized from year 2021-22 to 2022-23 highlighting the extension of Yoga based wellness services to more than 27 lakh people across the UT of J&K in the year 2021-22 and 2022-23. 74.3% of Yoga sessions have been conducted from the community platforms like AHWCs, Schools, workplaces etc. Yoga services can also be integrated with National Health Programs like NPCDCS, Mother and child health programs and National mental health program for wider and targeted reach for better public health outcomes.